PERANCANGAN APLIKASI POINT OF SALES BERBASISKAN CUSTOMER RELATIONSHIP MANAGEMENT PADA TOKO BUKU NOTRE-DAME - Gintoro, Gintoro; Widjaja, Edwin Hartanto (Bina Nusantara University, 2008)
Notre-Dame Bookshop is a company which growth is quite fast. For only 2 years, this bookshop hasopened 2 new branches. Unfortunately, this growth was not followed up by the development of company onsales system and shop marketing. Therefore, this research was conducted to facilitate all transaction in pointof sales from Notre-Dame Bookshop, and also to implement Customer Relationship Management (CRM)application in it. Research method used was a direct survey in field, a library study, an interview, aquestionaire, and a design method. The benefit of creating this application is to provide some solutions forproblem faced by Notre-Dame Bookshop, such as an easier recording of transaction, a more orderly andimposible to be lost managing of customers’ data, and a more practical and detailed reporting. Theconclusion got is with the existence of Customer Relationship Management (CRM) aplication integrated withpoint of sales, Notre-Dame Bookshop will be able to increase service to the customers by providing a fastand clear information, managing customers and company campaigne better, and obtaining details oftransaction faster and easier. Thus, the Notre-Dame Bookshop can be more sustained in creating their visionand mission.Keywords: point of sales, customer relationship management, company campaign